The researches on infectious bovine rhinotracheitis - infestious pustular vulvovaginitis (ibr/ipv) in bovines of konya livestock central research institute - Feridun Öztürk; Asuman Toker; Sibel Yavru (Eurasian Journal of Veterinary Sciences)
The 238 blood sera taken from cattle in Konya Livestock Central Research Institute were examined for antibodies to IBR / IPV virus by microneutralisation test. At the end of the test, at undiluted blood sera, the 134 cattle blood sera (56.30 %) were found seropositive for the neutralizing antibodies to IBR / IPV virus. The highest incidence of antibody was found in cattle over two years old. The 61 (45.52 %) of the 134 titrated positive sera showed a neutralizing antibody-titers in a range of 1:39.9 and 1:317. The cattle over two years old had the high antibody-titers.